Democracy's victory and crisis Nobel symposium no. 93 - Hadenius, Axel 1945- (Cambridge University Press, 1997)
The contributors to this volume, first published in 1997, address questions central to the development and survival of democratic rule. Brought together under the auspices of a Nobel Symposium on democracy, leading experts in the field examine historical experiences, social and cultural problems, economic development, constitutional issues, the impact of globalization, and the prospects for promoting democratic government. The coverage of the book is global, and the approach is multidisciplinary, providing a unique perspective from leading historians, political scientists, economists, and sociologists. The chapters thus provide an excellent survey of different facets of, and approaches to, democracy, including such fundamental issues as the nature of democratic citizenship, and its prevalence around the world; the relationship between economic development and the progress of democracy; and the influence of international interdependence on sovereignty and democratic accountability